TEOLOGI DALAM PEMUJAAN SIWA LINGGA - Ni Made Evi Kurnia Dewi (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2019)
Bali is an area that has a lot of culture, one of them in the form of phallus worship. phallus a is a symbol to worship Lord Shiva, This worship has a role and function that is quite important in the life of the Hindu community in Bali. he existence of phallus worship in Bali can be seen from the actions of the community to carry out the worship. Existence is the result of the social actions of the adherents, based on stimulus or response from the community to preserve the implementation of the phallus worship until it still exists until now. Implications or involvement of Hindus in the implementation of the worship of Shiva lingga in Bali, namely: 1). Increase sradha bhakti, sradha bhakti is done by way of Marga bhakti realized through arcanam namely worship in the form of media statues or pratimas. Increase beliefs about Hindu cosmology, Cosmology in the worship of the phallus places Lord Shiva the primary cause which lives the entire universe, the phallus is also believed to be the cause of creation, when the phallus is worshiped together with the yoni (phallus yoni) this pratima is believed to have two purusa powers and pradana, the meeting between these elements of power is believed to be able to create life in the universe